Помогите пожалуйста)
Преобразуйте в тождественно равное выражение:
1)1,3(х + 20у) - 40 (0,9у - х) + 63 у =
2)77(1,1а - 3b) - 3,2(4,5b - 50а) + 99а =

2

Ответы и объяснения

2014-01-16T22:27:46+00:00
1,3(х + 20у) - 40 (0,9у - х) + 63 у =1,3х+26у-36у+40х+63у=41,3х+53у
2)77(1,1а - 3b) - 3,2(4,5b - 50а) + 99а =84,7а-231b-14,4b+160a+99a=343.7a+245.4b
А правда, что если к 40 прибавить 1,3, то получится 38,7?
Комментарий удален
2014-01-16T22:54:14+00:00
1) 1,3(х +20у) - 40(0,9у - х) + 63у = 1,3х + 26у - 36у + 40х + 63у = 40,3х + 54у
2) 77(1,1а - 3b) - 3.2(4.5b - 50a) + 99a = 84.7a - 231b - 14.4b + 160a = 244.7a - 245.4b